Cinchona L. “Quina Tree”: Repopulation and reforestation in Peru - Albán-Castillo, Joaquina (2020)
This work focuses about the recent decisions made by the Ministry of Agriculture of Peru on the collection, propagation, and sowing of Cinchona species are reasons to point out the deficiencies of these decisions in light of advances in the knowledge of Cinchona taxonomy and systematics. We emphasize the role of the science analysing and informing about decisions in the sustainable use of natural resources.